2000
DOI: 10.1109/52.820015
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking software development productivity

Abstract: 0 I E E E S O F T WA R E J a n u a r y / F e b r u a r y 2 0 0 0 0 7 4 0 -7 4 5 9 / 0 0 / $ 1 0 . 0 0 © 2 0 0 0 I E E E factors affect software-development productivity in any given environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 125 publications
(78 citation statements)
references
References 6 publications
2
75
1
Order By: Relevance
“…As was discussed in section 2, a similar productivity analysis was carried out by Maxwell and Forselius [16] ined data from a total of 206 projects from 26 companies. We refer to this as the FinnishMF data set.…”
Section: Productivity Trends Over Timementioning
confidence: 99%
See 4 more Smart Citations
“…As was discussed in section 2, a similar productivity analysis was carried out by Maxwell and Forselius [16] ined data from a total of 206 projects from 26 companies. We refer to this as the FinnishMF data set.…”
Section: Productivity Trends Over Timementioning
confidence: 99%
“…This is our vantage point. Our main motivation is a previous study conducted by Maxwell and Forselius [16] on an older version of the same data set that we use. In their study, Maxwell and Forselius found Company and Business Sector as the most important variables in explaining productivity.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations